2015
DOI: 10.1016/j.mrgentox.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pig-a mutant erythrocytes in male and female rats exposed to 1,3-propane sultone, ethyl carbamate, or thiotepa

Abstract: Validation of the Pig-a gene mutation assay has been based mainly on studies in male rodents. To determine if the mutagen-induced responses of the X-linked Pig-a gene differ in females compared to males, groups of five male and female Sprague Dawley rats were exposed to the mutagens 1,3-propane sultone (80 mg/kg/day), ethyl carbamate (600 mg/kg/day), or thiotepa (7.5 mg/kg/day) for three consecutive days (study Days 1-3). Pig-a mutant phenotype reticulocyte (RETCD59-) and mutant phenotype erythrocyte (RBCCD59-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It is noteworthy that EC caused a significant induction of Pig‐a mutant cells: increased RET CD59− and RBC CD59− frequencies were noted in both the 3‐day and 28‐day studies. The kinetics and magnitude of the mutant cell responses in the 3‐day and 28‐day studies were very similar to those shown in an experiment conducted by Labash et al () in male and female rodents exposed to 600 mg/kg/day EC for 3 consecutive days and the research of Bemis et al () in rats dosed orally for 28 consecutive days with 250 mg/kg/day EC. However, the maximal mutation frequency of RET in our 28‐day treatment study with EC (150–300 mg/kg/day), an ~13.2‐fold increase over the control, was lower than the ~74.0‐fold increase in a similar study conducted by Stankowski et al (), where SD rats were treated orally with 25–250 mg/kg/day using the same dosing protocol; while the maximal ~26.4‐fold increase over the control for mutant RBC in our study is greater than the ~8.1‐fold increase in the study of Stankowski et al ().…”
Section: Discussion and Summarysupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that EC caused a significant induction of Pig‐a mutant cells: increased RET CD59− and RBC CD59− frequencies were noted in both the 3‐day and 28‐day studies. The kinetics and magnitude of the mutant cell responses in the 3‐day and 28‐day studies were very similar to those shown in an experiment conducted by Labash et al () in male and female rodents exposed to 600 mg/kg/day EC for 3 consecutive days and the research of Bemis et al () in rats dosed orally for 28 consecutive days with 250 mg/kg/day EC. However, the maximal mutation frequency of RET in our 28‐day treatment study with EC (150–300 mg/kg/day), an ~13.2‐fold increase over the control, was lower than the ~74.0‐fold increase in a similar study conducted by Stankowski et al (), where SD rats were treated orally with 25–250 mg/kg/day using the same dosing protocol; while the maximal ~26.4‐fold increase over the control for mutant RBC in our study is greater than the ~8.1‐fold increase in the study of Stankowski et al ().…”
Section: Discussion and Summarysupporting
confidence: 86%
“…Although the two test chemicals in our study, PCZ and EC, have been investigated previously in similar integrated studies as well as assays measuring single genotoxicity endpoints, including Pig‐a gene mutation (Phonethepswath et al, ; Bemis et al, ; Labash et al, ; Stankowski et al, ; Pu et al, ; Revollo et al, ), the data reported herein allow comparisons between the responses for multiple genotoxicity endpoints as a function of two commonly employed treatment regimens (short‐term, 3‐day and subchronic, 28‐day studies). In addition to conducting multiple genotoxicity assays, analyses were made to collect data for hematology, clinical chemistry, organ weight, and other general toxicity indicators.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…No clear sex bias has been found for Pig‐a mutation in rodent studies (Labash et al ; Labash et al ), while studies in different ethnic human populations have produced inconsistent results (Dobrovolsky et al ; Dertinger et al ; Cao et al ). The Pig‐a gene is on the X chromosome, suggesting that X‐chromosome inactivation in females may affect spontaneous MFs.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy young adult rats, usually 6-10 weeks old at the start of dosing, are used. Male or female rats can be used for this assay [29][30][31]. Groups of 6 rats are recommended at the 6th IWGT Workgroup meeting.…”
Section: Animals and Dosingmentioning
confidence: 99%